Celebrating the source water festivities of Southeast Asia - Poh, Lindy ([Jakarta, Indonesia] Association of Southeast Asian Nations Committee on Culture and Information (ASEAN-COCI), 2009)
"This book features the iconic and beloved water celebrations of the ASEAN countries as well as introduces the lesser known rituals and festivities that have shaped the cultural and social life of the region."--Publisher's website.
Includes index.
Keywords: Festivals -- Southeast Asia; Festivals -- Southeast Asia -- Pictorial works; Water and civilization; Water and civilization -- Pictorial works; Water|z -- Southeast Asia -- Religious aspects; Water -- Southeast Asia -- Religious aspects -- Pictorial works